Electrophoresis and electroosmosis as determined on the level of a single isolated colloid by use of optical tweezers - Semenov, Ilya; Kremer, Friedrich (Diffusion Fundamentals, 2015)
Experiments are described on the electrophoretic mobility of a single isolated colloid and the electro-osmotic response of the surrounding medium. For that optical tweezers are employed which enable one to trap a particle without any mechanical contact and to measure its position and the forces acting on it with high resolution (±2 nm, ±200 fN). In a custom-made microfluidic cell, the two effects are separated using the identical colloid. The electrophoretic response is found to be 5 times stronger than the electroosmotic effect. It is phase-shifted with respect to the external electric field, hence giving rise to a complex electrophoretic mobility which can be theoretically described by a strongly damped driven harmonic oscillator model. The measured electrophoretic mobility in monovalent salt is found to be in agreement with computations combining primitive model molecular dynamics simulations of the ionic double layer with the standard electrokinetic model. Mobility reversal of a single colloid is observed for trivalent ionic solutions (LaCl3) at ionic strengths > 10−2 mol/l. The latter is in quantitative agreement with a numerical model in which ion specific attractive forces are taken into consideration.